Microbial Community Changes in the Rhizosphere Soil of Healthy and Rusty Panax ginseng and Discovery of Pivotal Fungal Genera Associated with Rusty Roots. (16th January 2020) - Wei, Xuemin; Wang, Xiaoyue; Cao, Pei; Gao, Zitong; Chen, Amanda Juan; Han, Jianping
Abstract : Panax ginseng Meyer, a valuable medicinal plant, is severely threatened by rusty root, a condition that greatly affects its yield and quality. Studies investigating the relationship between soil microbial community composition and rusty roots are vital for the production of high-quality ginseng. Here, high-throughput sequencing was employed to systematically characterize changes in the soil microbial community associated with rusty roots. Fungal diversity was lower in the soils of rusty root-affected P. ginseng than in those of healthy plants. Importantly, principal coordinate analysis separated the fungal communities in the rhizosphere soils of rusty root-affected ginseng from those of healthy plants. The dominant bacterial and fungal genera differed significantly between rhizosphere soils of healthy and rusty root-affected P. ginseng, and linear discriminant analysis effect size (LEfSe) further indicated a strong imbalance in the soil microbial community of diseased plants. Significantly enriched bacterial genera (including Rhodomicrobium, Knoellia, Nakamurella, Asticcacaulis, and Actinomadura ) were mainly detected in the soil of rusty root-affected P. ginseng, whereas significantly enriched fungal genera (including Xenopolyscytalum, Arthrobotrys, Chalara, Cryptococcus, and Scutellinia ) were primarily detected in the soil of healthy plants. Importantly, five fungal genera ( Cylindrocarpon, Acrophialophora, Alternaria, Doratomyces, and Fusarium ) were significantly enriched in the soil of rusty root-affected plants compared with that of healthy plants, suggesting that an increase in the relative abundance of these pathogenic fungi ( Cylindrocarpon, Alternaria, and Fusarium ) may be associated with ginseng rusty roots. Additionally, this study is the first to report that an increase in the relative abundances of Acrophialophora and Doratomyces in the rhizosphere of P. ginseng may be associated with the onset of rusty root symptoms in this plant. Our findings provide potentially useful information for developing biological control strategies against rusty root, as well as scope for future screening of fungal pathogens in rusty roots of P. ginseng .